(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2025)
The modern world market for agricultural feed materials is experiencing high price volatility. The increase in energy prices, especially for coal and natural gas, resulted in a sharp increase in the costs of agricultural inputs, including fertilizers. Agricultural production is a risky business, and managing different risks is challenging for farmers. The risk concerning agricultural production is a particularly complex phenomenon, not only due to the volume of threats, and fragmentation of producers but also due to the unpredictable variability of phenomena. Derivatives are only of value in an environment that is vulnerable to changes. Using this type of tool in business activity enables agribusiness entities to effectively manage the price risk and at the same time stabilize the achieved income. This study is mainly focused on the Farmer-Investor’s perception of Benefits of Investment in Agricultural Derivative Markets. A Chi-Square test was run, and SPSS was used to assess the association between Age, Gender, Education, Farmer Type, and Benefit of Investments in Agricultural Commodity Derivative Markets in India. It was found that there was no association between Independent and Dependent variables in the said study and therefore Policy should be devised to make people aware of the Benefits these Commodity markets provide.